2009
DOI: 10.1007/bf03246163
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of chromium(III) ion-selective electrodes based on N,N-bis(salicylidene)-o-phenylenediaminatechromium(III)

Abstract: A comparative study was made between three types of Cr(III) ion-selective electrodes: PVC membrane electrode, silver coated electrode and modified carbon paste electrode based on N,N-bis(salicylidene)-o-phenylenediaminatechromium(III) complex (Crsalophen). As anticipated, electrodes with a solid contact, rather than a traditional liquid inner contact, give lower detection limits because of diminished ion fluxes. Often, however, ill-defined solid contact gives rise to instabilities and interferences by oxygen g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Other studies have reported a wide optimum working pH range of 2.0–9.0, 9 4.5–8.0, 23 and 1.7–6.5 24 for recently introduced Cr(III) ion‐selective sensors. Considering the chemistry of trivalent chromium and the chemical species of Cr(III) at different pHs, a pH range of 4.0–6.5 was selected as the optimum working pH of the electrode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported a wide optimum working pH range of 2.0–9.0, 9 4.5–8.0, 23 and 1.7–6.5 24 for recently introduced Cr(III) ion‐selective sensors. Considering the chemistry of trivalent chromium and the chemical species of Cr(III) at different pHs, a pH range of 4.0–6.5 was selected as the optimum working pH of the electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the variation of the electrode response at basic solutions may be due to metal ions hydrolysis and the formation of soluble/insoluble hydroxyl complexes. 12 Other studies have reported a wide optimum working pH range of 2.0-9.0, 9 4.5-8.0, 23 and 1.7-6.5 24 for recently introduced Cr(III) ionselective sensors. Considering the chemistry of trivalent chromium and the chemical species of Cr(III) at different pHs, a pH range of 4.0-6.5 was selected as the optimum working pH of the electrode.…”
Section: The Effect Of Ph On the Electrode Responsementioning
confidence: 99%
“…In addition, they should have good solubility in the paste matrix and sufficient lipophilicity to prevent leaching from the paste into the sample solution. 45 The ion-exchangers KT-ST, KT-SM, KT-PT, KT-PM and KT-TPB were prepared and tested as modiers for the present electrode. The inuence of the amount of the different ketamine ion-exchangers in the carbon paste was investigated, and the corresponding results are summarized in Table 1.…”
Section: Effect Of Ion-exchangermentioning
confidence: 99%
“…Ion-exchanger complex used in ISEs should have rapid exchange kinetics and adequate formation constants in the paste. In addition, they should have good solubility in the paste matrix and sufficient lipophilicity to prevent leaching from the paste into the sample solution [22,23].…”
Section: Effect Of Ion-exchangermentioning
confidence: 99%